Heart failure awareness survey in Germany: general knowledge on heart failure remains poor. (22nd March 2017) - Zelenak, Christine; Radenovic, Sara; Musial‐Bright, Lindy; Tahirovic, Elvis; Sacirovic, Mesud; Lee, Chong‐Bin; Jahandar‐Lashki, Diana; Inkrot, Simone; Trippel, Tobias Daniel; Busjahn, Andreas; Hashemi, Djawid; Wachter, Rolf; et al.
Abstract: Aims: Previous studies demonstrated poor public awareness of heart failure (HF) compared with myocardial infarction and stroke. With respect to several activities to improve HF awareness in recent years, we present data on the development of HF awareness and information sources in Germany over 8 years. Methods and results: In 2007, 2012, and 2015, respectively, 2531, 359, and 171 respondents answered questions about causes, presentation, prognosis, and treatment of HF from a survey developed by the German Competence Network HF. Relationships between respondents' sociodemographic data and their HF knowledge were explored and changes in knowledge and use of information sources analysed. Sixty‐eight per cent of respondents knew HF as 'weakness of the heart'. Seventy‐nine per cent knew shortness of breath, 74% reduced exercise tolerance, and 52% knew leg edema as symptoms. Only 40% knew all three symptoms. Although up to 34% of the respondents were directly or indirectly affected by HF, they demonstrated poor knowledge about severity and prognosis. Between 2007 and 2015, overall HF awareness has not changed; awareness about treatment has dropped significantly. Younger respondents used all media, especially internet, for information about health; older respondents preferred printed/verbal media and their physician. Conclusions: We found rather insufficient public knowledge on HF etiology and symptoms but especially about management, severity, and prognosis, which is essential for good self‐care and adherence of patients. Heart failure awareness has not improved even though awareness campaigns were held over the years. It seems that especially older patients should be much more approached by their family physicians.